How productive are capital investments in Europe? - Patrick Vanhoudt; Thomas Mathä; Bert Schmid (EIB Papers, 2000)
Economists agree at least on this: it is difficult to find evidence for, or merely to imagine any growth mechanism that does not work through the increase of a stock of capital in one way or another. From a more policy point of view - in particular in terms of the debate of economic development and convergence in standards of living - an important question then is when spending on investment is best done by the government itself, and when public funds should be used to support investment by the private sector. A key concept in this issue is the degree of external benefits, or spillovers, of investment. These notions refer to the fact that sometimes a certain action by an economic agent results indirectly in productivity gains for others that cannot be completely captured by the principal investor in his price setting behaviour.
Keywords: 330; Investition; Öffentliche Investition; Produktivität; Regionale Disparität; Humankapital; Faktormobilität; Entwicklungskonvergenz; EU-Staaten